2010
DOI: 10.1007/s11270-010-0603-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Microbial Functional Diversity and Activity in Paddy Soils Irrigated with Industrial Wastewaters in Bandung, West Java Province, Indonesia

Abstract: Characteristics, such as microbial biomass, basal respiration, and functional diversity of the microbial communities, were investigated in paddy soils located in Bandung, West Java Province, Indonesia, that have been heavily polluted by industrial effluents for 31 years. Paddy soil samples (10-20 cm) were taken from two sites: polluted soils and unpolluted soils (as control sites). The polluted soils contained higher salinity, higher sodicity, higher nutrient contents, and elevated levels of heavy metals (Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…CEC is related to heavy metal toxicity affecting microorganism activities in soils [30]. The CEC depends on the amount and type of hydrous metal oxides and organic matter.…”
Section: Correlation Analysismentioning
confidence: 99%
“…CEC is related to heavy metal toxicity affecting microorganism activities in soils [30]. The CEC depends on the amount and type of hydrous metal oxides and organic matter.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Fire disturbance leads to the change of soil environment, which can be attributed to an increase in grass functional group coverage and biomass, root‐to‐soil ratio and soil physical–chemical property. The fire disturbance also changes the soil organic quality and quantity of the utilisation of C and N. Changes in the physical and chemical soil properties were reflected by changes in the microbial communities and their activities (Chaerun et al ., ). In this study, we found that the total PLFA, G + bacterial PLFA and G − bacterial PLFA are closely related to plant community characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Tree peony can continually provide soil microbes with nutritive materials by releasing root exudates and rhizodeposits. In addition, the changes in soil chemical properties resulting from continued tree peony growth have lasting impacts on soil microbial communities and functional diversity (Chaerun et al, 2011). Moreover, the reduction in the functional diversity of the microbial community resulting from continued growth may also be ascribed to differences in root exudation, because the quantity and chemical composition of root exudates change over the course of tree peony growth (Marschner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%